The Soul of a Butterfly : Reflections on Life's Journey - Ali, Muhammad and Hana Yasmeen Ali (New York Simon & Schuster, 2004)
"Former boxing legend Muhammad Ali, one of the best-known and best-loved celebrities and an international good-will ambassador, offers inspiration and hope as he describes the spiritual philosophy that sustains him"
Include Illustrations
Keywords: Boxers (Sports) -- Spiritual biography